Model peramal kepuasan kerja pegawai perkhidmatan pendidikan di komuniti pesisir Terengganu - Muda, Mohd Shaladdin; Omar, Nik Wan (Universiti Utara Malaysia, 2006)
This research critically analyses the determinants of job satisfaction and their relationship with the organizational behavior factor for teachers in Malaysia.Its purpose is to provide suggestions to the relevant parties in offering the best teachers’ scheme and ultimately, the clients will enjoy the best and quality educational service. The issue of job satisfaction has become extremely crucial because of late there have been numerous complaints from teachers regarding incentives, long working hours, job burden, job stress, job environment as well as relationships with students’ families. This research focuses on three main factors related to job satisfaction namely: the organization factor, the demographic factor and the behavior factor. The organizational factor encompasses variants such as the job itself, salary and incentives, promotion,job condition and environment, colleagues, communication, supervision and job procedure. The demographic factors such as age, gender, work experience, academic qualification and work place are used as moderator variants. The behavior factor comprises job motivation, stress, commitment, involvement,loyalty and job performance. The initial findings show that there is a positive correlation between the above variants and teachers’ satisfaction. There is a significant relationship between job satisfaction and the demographic factors, between job satisfaction and the organizational factors, and between job satisfaction and the behavior factors. The research respondents were teachers of government schools around the coastal areas in Terengganu. Hopefully the research findings can offer an alternative in producing the best educational working team which can fulfill the society’s and the nation’s aspirations as well as becoming a base for negotiations between teachers and the relevant parties regarding service terms to reach a common goal. It is also hoped that the implementation of the research findings can create a win-win situation among the government, teachers, students and the public who are the clients of the educational service. In addition, the research findings can be added to the literature in this field.